Penerapan Model Rasional dalam Pengambilan Keputusan Kepala Sekolah pada Era Kurikulum Merdeka - Agung Setiabudi; Nurmalisa; M. Rizki Danuarta; Yeni Lestari (Indra institute Research & Publication, 2025)
This study examines the application of the rational model in principal decision-making in the Merdeka Curriculum era, which demands that educational units be more adaptive, contextual, and data-driven. The need to improve the quality of school management through a systematic and objective decision-making process underlies this study. The study aims to explain the concept of the rational model, analyze its relevance to the implementation of the Merdeka Curriculum, and identify its implications for management and educational quality in schools. The method used is a literature review by systematically reviewing scientific sources according to the study's focus. The analysis results indicate that the rational model provides a structured decision-making framework through the stages of problem identification, alternative analysis, priority setting, and selecting the best data-based decision. This model aligns with the principles of the Merdeka Curriculum, which prioritizes the autonomy of educational units and student-centered learning. Furthermore, the literature review illustrates that principals have a strategic role as policy directors to ensure every decision supports the effectiveness of learning and school management. The conclusion indicates that the application of the rational model strengthens accountability, transparency, and the quality of educational management. With a measured and evidence-based approach, schools can establish policies that are consistent, relevant, and aligned with learning needs in the context of the Merdeka Curriculum.